Luminescence Properties of Epitaxial Cu2O Thin Films Electrodeposited on Metallic Substrates and Cu2O Single Crystals - Trinkler, Laima; Dai, Dajin; Chang, Liuwen; Chou, Mitch Ming-Chi; Wu, Tzu-Ying; Gabrusenoks, Jevgenijs; Nilova, Dace; Ruska, Rihards; Berzina, Baiba; Nedzinskas, Ramunas (MDPI, 2023)
The luminescent properties of epitaxial Cu2O thin films were studied in 10–300 K temperature range and compared with the luminescent properties of Cu2O single crystals. Cu2O thin films were deposited epitaxially via the electrodeposition method on either Cu or Ag substrates at different processing parameters, which determined the epitaxial orientation relationships. Cu2O (100) and (111) single crystal samples were cut from a crystal rod grown using the floating zone method. Luminescence spectra of thin films contain the same emission bands as single crystals around 720, 810 and 910 nm, characterizing (Formula presented.), (Formula presented.) and (Formula presented.) defects, correspondingly. Additional emission bands, whose origin is under discussion, are observed around 650–680 nm, while the exciton features are negligibly small. The relative mutual contribution of the emission bands varies depending on the thin film sample. The existence of the domains of crystallites with different orientations determines the polarization of luminescence. The PL of both Cu2O thin films and single crystals is characterized by negative thermal quenching in the low-temperature region; the reason of this phenomenon is discussed. © 2023 by the authors. --//-- Trinkler L., Dai D., Chang L., Chou M.M.-C., Wu T.-Y., Gabrusenoks J., Nilova D., Ruska R., Berzina B., Nedzinskas R.; Luminescence Properties of Epitaxial Cu2O Thin Films Electrodeposited on Metallic Substrates and Cu2O Single Crystals (2023) Materials, 16 (12), art. no. 4349; DOI: 10.3390/ma16124349; https://www.scopus.com/inward/record.uri?eid=2-s2.0-85163722368&doi=10.3390%2fma16124349&partnerID=40&md5=91eba1b1a1b09daf1a206d63adf0f7ed. Published under the CC BY 4.0 licence.
The financial support of M-ERA.NET project “ZnMgO materials with tunable band gap forsolar-blind UV sensors” (ZMOMUVS) and the post-doctoral research project “Growth and characterisation of Ga2O3 and ZnMgO thin films for solar-blind ultraviolet applications” (R. Nedzinskas; research application no.: 1.1.1.2/VIAA/3/19/442) is acknowledged. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Program H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART2. The electrodeposition and related characterization works were also supported by the Ministry of Science and Technology of the Republic of China (MOST 107-2221-E-110-004-MY3).
Keywords: Research Subject Categories::NATURAL SCIENCES; cuprous oxide; electrodeposition; epitaxial thin films; optical absorption; photoluminescence; single crystal